Analisis Pertumbuhan Laba Pada PT. Toba Pulp Lestari Tbk - Agustina Br. Tungkir; Mila Yulia Herosian; Maria Cendika Manalu; M. Alvi Syahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine and analyze profit growth on financial ratios Current Ratio, Debt To Assets Ratio, and Total Assets Turn Over at the company PT. Toba Pulp Lestari Tbk. This research method is quantitative method with quantitative descriptive research. Data collection techniques using documentation techniques. The independent variables in this study are the Current Ratio, Debt To Assets Ratio, and Total Assets Turn Over. The dependent variable in this study is profit growth. Data analysis used multiple linear regression analysis. The results of this study indicate that the F test value obtained is Fcount of 5.571 with a significant value of 0.065>0.05. The results of the T test show, a) the CR variable has a tcount of -0.099 with a significant value of 0.926>0.05; b) the DAR variable has a value of -tcount< ttable that is -3.662<2.0150; c) the TATO variable has a tcount of -0.916 with a significant value of 0.411>0.05. In conclusion, partially Current Ratio, Debt To Assetsratio, and Total Assets Turn Over have no effect on profit growth at PT. Toba Pulp Lestari Tbk. Simultaneously Current Ratio, Debt To Assets Ratio, and Total Assets Turn Over together affect profit growth at PT. Toba Pulp Lestari Tbk. Keywords: Current Ratio, Debt to Assets Ratio, Profit Growth, Total Assets Turn Over